Modulation of the major histocompatibility complex class II-associated peptide repertoire by human histocompatibility leukocyte antigen (HLA)-DO. - van Ham, M; van Lith, M; Lillemeier, B; Tjin, E; Grüneberg, U; Rahman, D; Pastoors, L; van Meijgaarden, K; Roucard, C; Trowsdale, J; Ottenhoff, T; Pappin, D; et al. (2000)
Antigen presentation by major histocompatibility complex class II molecules is essential for antibody production and T cell activation. For most class II alleles, peptide binding depends on the catalytic action of human histocompatibility leukocyte antigens (HLA)-DM. HLA-DO is selectively expressed in B cells and impedes the activity of DM, yet its physiological role remains unclear. Cell surface iodination assays and mass spectrometry of major histocompatibility complex class II-eluted peptides show that DO affects the antigenic peptide repertoire of class II. DO generates both quantitative and qualitative differences, and inhibits presentation of large-sized peptides. DO function was investigated under various pH conditions in in vitro peptide exchange assays and in antigen presentation assays using DO(-) and DO(+) transfectant cell lines as antigen-presenting cells, in which effective acidification of the endocytic pathway was prevented with bafilomycin A(1), an inhibitor of vacuolar ATPases. DO effectively inhibits antigen presentation of peptides that are loaded onto class II in endosomal compartments that are not very acidic. Thus, DO appears to be a unique, cell type-specific modulator mastering the class II-mediated immune response induced by B cells. DO may serve to increase the threshold for nonspecific B cell activation, restricting class II-peptide binding to late endosomal compartments, thereby affecting the peptide repertoire.